Stilbene Switch Activated by Click Chemistry. (2017) - Zhou, Yubin; Wu, Yuanyuan; Pokholenko, Oleksandr; Papper, Vladislav; Marks, Robert S.; Steele, Terry W.J.
Abstract: Stilbenes have not been widely regarded as fluorophore labels due to their difficulty in conjugation. Quenched fluorescence of maleimide functionalized stilbene is found to be restored after thiol binding, enabling separation-free fluorophore labelling.